An Asian perspective and the New Zealand Treasury Living Standards Framework - Sue Young (New Zealand Government, The Treasury, 2018)
The New Zealand Treasury has developed a Living Standards Framework (LSF) to assess the impact of government policies on intergenerational wellbeing. The Treasury is committed to incorporating New Zealand's diverse cultural perspectives into the LSF framework (Frieling, 2018, p. 2). This report is a starting point for discussions on ways to include an Asian perspective in the LSF. The paper references work by academics, health practitioners, and experts in New Zealand and overseas since the LSF is based on the OECD approach. As one of the four largest demographic groups in New Zealand, projected to be the second largest by 2026, a New Zealand Asian perspective on the LSF is critical. The Asian culture strongly values collectivism, often with hierarchical relationships and distinct gender roles. Collectivist cultures strongly emphasize the needs and goals of the group as a whole over the needs and desires of individuals. In such cultures, relationships with other members of the group and the interconnectedness between people play a central role in each person's identity and wellbeing. The Confucian teachings which emphasise diligence, perseverance, frugality, responsibility and recognition of the hierarchical orderings of relationship have also heavily influenced the Asian cultural values and perceptions of wellbeing. Hence, from the view of the LSF, the Asian culture place much emphasis on Social and financial/physical capital.
Keywords: 330